2014
DOI: 10.3390/polym7010047
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Nanoparticle Adsorption as Fire-Protection Approach for Fabrics

Abstract: Abstract:The present paper critically analyzes the potential for commercially available nanoparticles for enhancing the flame-retardant properties of synthetic and natural fabrics and their corresponding blends. Each nanoparticle has been applied to the fabric through a finishing-like process (namely impregnation/exhausting or, more simply, nanoparticle adsorption) in aqueous media and the resulting properties of these fabrics have been assessed in terms of combustion behavior by use of a cone calorimeter unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 16 publications
1
43
0
1
Order By: Relevance
“…It was observed that formed CSE particles have a uniform size distribution with a mean volume diameter of 30 nm (standard deviation 0.98). The use of nanoparticles in the flame retardancy field has shown encouraging results and seems to be a good alternative in particular when applied as coatings on fabric surfaces [29][30][31]. Nanoparticles can be directly synthesized in situ on the fibers and fabric surfaces through techniques such as solgel processes, or preformed nanoparticles can be deposited on the fabric surface by using layer-by-layer (LbL) assembly or nanoparticle adsorption [29].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that formed CSE particles have a uniform size distribution with a mean volume diameter of 30 nm (standard deviation 0.98). The use of nanoparticles in the flame retardancy field has shown encouraging results and seems to be a good alternative in particular when applied as coatings on fabric surfaces [29][30][31]. Nanoparticles can be directly synthesized in situ on the fibers and fabric surfaces through techniques such as solgel processes, or preformed nanoparticles can be deposited on the fabric surface by using layer-by-layer (LbL) assembly or nanoparticle adsorption [29].…”
Section: Resultsmentioning
confidence: 99%
“…However, in order to make the present review on cotton ame retardancy for the best comprehension, the results currently updated regarding nanoparticle adsorption, LbL and sol-gel have been summarised in Tables 8-12. In addition, Table 13 reports the main results achieved depositing new green coatings consisting of bio-macromolecules like proteins and nucleic acids. 109 From an overall consideration, all the nanoparticles under study showed similar behaviour in that they improve cotton re performance to varying degrees; in particular, they promoted an increase of TTI (like in the case of sodium cloisite, hydrotalcite, 110 boehmite and POSS® 111 ), a reduction of pkHRR (all nanoparticles cited in Table 8) or both these events. 107 3.2.1 Nanoparticle adsorption.…”
Section: Present: From 2010 To Todaymentioning
confidence: 84%
“…Based on an increasing value for FPI, the next ranking has been recently established 109 (Fig. Based on an increasing value for FPI, the next ranking has been recently established 109 (Fig.…”
Section: Present: From 2010 To Todaymentioning
confidence: 99%
“…They should also present environmental-friendly and nontoxic features. Although their efficiency is lower than halogen based flame retardants, expensive phosphorus based flame retardants for polyester are preferred, because of low smoke generation, nontoxicity, and low corrosion properties [10][11][12]. On the other hand, melt dripping of polyester during burning is still a major problem.…”
Section: Advances In Polymer Technologymentioning
confidence: 99%
“…Thus, very few studies related to the cone calorimeter analyses of textiles have been found in literature. Alonghi et al [12] applied several nanoparticles and their combinations to polyester, cotton, and polyester/cotton blends and tested their flammability by cone calorimeter under a heat flux of 35 kW/m 2 . They have investigated that most of the nanoparticles increase the fire performance index (FPI) value of polyester fabric with low area density (171 g/m 2 ); however they had very little effect on polyester fabric with high area density (490 g/m 2 ).…”
Section: Advances In Polymer Technologymentioning
confidence: 99%